Analysis of Codification Ability and Readiness for Field Clinic Practice of ITSK Hospital Students dr. Soepraoen - Wahandika, Akbar Novando Putra; Rusdi, Achmad Jaelani; Slamet Suhariyono, Untung (PROMOTOR, 2025)
Field Work Practice (PKL) is an important part of the education of the Medical Records and Health Information Study Program (RMIK) to hone students' skills in the real world of work. The ability to code diagnoses, as the main competency in the Codification and Classification of Diseases and Health Problems (KKPMT) course, is very important for RMIK students. Student readiness in street vendors is a key factor in determining the quality of graduates. Preliminary studies show that D3 RMIK ITSK RS. Dr. Soepraoen Hospital batch 2022-2023 students are not fully ready to undergo street vendors, especially in the practical application of KKPMT materials. This study aims to analyze the relationship between clinical codification ability and street vendor readiness. The method used was quantitative with a cross-sectional approach, involving 120 respondents through total sampling. Data were collected using a questionnaire that measured clinical codification ability (independent variable) and street vendor readiness (dependent variable). Data analysis using the Kendall test Tau_b showed very high questionnaire reliability (Cronbach's Alpha = 1,000). The results showed a weak negative relationship between clinical codification ability and street vendor readiness (correlation coefficient = -0.115), but not statistically significant (p-value = 0.125 > 0.05). This means that there is no significant relationship between the two variables, so H1 is rejected and H0 is accepted. These findings indicate that other factors, such as communication skills, mastery of other materials, or previous practical experience, may have more influence on street vendor readiness. This research is the basis for exploring other factors that affect students' readiness to face street vendors.